An In-Depth Study of Multiple Cropping Farming Systems: The Impact on Cocoa Farmers’ Income - Akhsan Akhsan; Muhammad Arsyad; Achmad Amiruddin; Muslim Salam; Nurlaela Nurlaela; Muhammad Ridwan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Multiple cropping farming systems affect farmers' income and have become a serious determinant in agricultural development. The diversity of information received by the farmers including multiple cropping can provide new knowledge, which will in turn influence productivity and income. Therefore, this study aims to evaluate the benefits of multiple cropping and its economic impact on cocoa farmers' income. It was conducted using the Ordinary Least Square Method to estimate parameters and RC Ratio for income comparison from the farming systems. The results showed that the choice of farmers in cropping patterns and types of crops is aimed at avoiding crop failure. The advantage of multiple cropping is that the use of soil nutrients is more effective because plants grow together on the same land. It also provides a higher income compared to monocropping and tends to reduce operational costs. Among the five factors evaluated, only three influenced farmers' income through extension activities. They are information on credit amount obtained, level of heterogeneity, and agricultural production. These factors are important aspects of communication activities that can increase knowledge in a heterogeneous environment of multiple cropping systems, which will, in turn, improve farmers' income.